2020
DOI: 10.1111/mcn.12929
|View full text |Cite
|
Sign up to set email alerts
|

Water insecurity potentially undermines dietary diversity of children aged 6–23 months: Evidence from India

Abstract: Dietary diversity is a crucial pathway to child nutrition; lack of diversity may deprive children of critical macro and micronutrients. Though water along with hygiene and sanitation is a known driver of child undernutrition, a more direct role of household water in shaping dietary diversity remains unexplored. Existing literature provides a sound theoretical basis to expect that water could affect dietary diversity among young children. Here, we test the proposition that suboptimal household access to water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Household access to water was ranked among the five most important predictors of children’s attainment of MDD in our dominance analysis, further highlighting the importance of the former on the latter. Our finding is consistent with that of Choudhary et al, who found that suboptimal household water access was associated with a lower probability of a child achieving MDD in India [ 26 ]. Household water access can also affect children’s attainment of MDD through gendered and competing demands on caregivers’ time [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Household access to water was ranked among the five most important predictors of children’s attainment of MDD in our dominance analysis, further highlighting the importance of the former on the latter. Our finding is consistent with that of Choudhary et al, who found that suboptimal household water access was associated with a lower probability of a child achieving MDD in India [ 26 ]. Household water access can also affect children’s attainment of MDD through gendered and competing demands on caregivers’ time [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is consistent with that of Choudhary et al, who found that suboptimal household water access was associated with a lower probability of a child achieving MDD in India [ 26 ]. Household water access can also affect children’s attainment of MDD through gendered and competing demands on caregivers’ time [ 26 ]. The results from a 19-site cross-cultural study by Schuster and colleagues found that household water insecurity was qualitatively associated with children’s delayed feeding.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To date, data suggest stronger plausibility that water insecurity is a driver of food insecurity than the other way around (Boateng et al, 2020;Brewis et al, 2020). Additionally, cross-cultural qualitative data support the notion that increased household water insecurity affects maternal and child feeding practices and breastfeeding practices, which may lead to variation in risk of dehydration of children or malnutrition (Schuster et al, 2020). Moreover, one dimension of water insecurity, water access, was associated with meeting minimum dietary diversity guidelines in India among infants aged 6-23 months (Choudhary et al, 2020).…”
Section: Food Insecurity and Inadequate Nutritional Intakementioning
confidence: 90%